A feasibility study of the Xpert MTB/RIF test at the peripheral level laboratory in China - Xichao Ou; Hui Xia; Qiang Li; Yu Pang; Shengfen Wang; Bing Zhao; Yuanyuan Song; Yang Zhou; Yang Zheng; Zhijian Zhang; Zhiying Zhang; Junchen Li; et al. (International Journal of Infectious Diseases, 2015)
Objective: To evaluate the performance of Xpert MTB/RIF (MTB/RIF) in the county-level tuberculosis (TB) laboratory in China. Methods: From April 2011 to January 2012, patients with suspected multidrug-resistant tuberculosis (MDR-TB) and non-MDR-TB were enrolled consecutively from four county-level TB laboratories. The detection of Mycobacterium tuberculosis (MTB) by MTB/RIF was compared to detection by Löwenstein–Jensen culture. The detection of rifampin resistance was compared to detection by conventional drug-susceptibility testing. The impact of multiple specimens on the performance of MTB/RIF was also evaluated. Results: A total of 2142 suspected non-MDR-TB cases and 312 suspected MDR-TB cases were enrolled. For MTB detection in suspected non-MDR-TB cases, the sensitivity and specificity of MTB/RIF were 94.4% and 90.2%, respectively. The sensitivity in smear-negative patients was 88.8%. For the detection of rifampin resistance in suspected non-MDR-TB cases, the sensitivity and specificity of MTB/RIF were 87.1% and 97.9%, respectively. For the detection of rifampin resistance in suspected MDR-TB cases, the sensitivity and specificity of MTB/RIF were 87.1% and 91.0%, respectively. Using multiple sputum specimens had no significant influence on the performance of MTB/RIF for MTB detection. Conclusions: The introduction of MTB/RIF could increase the accuracy of detection of MTB and rifampin resistance in peripheral-level TB laboratories in China. One single specimen is adequate for TB diagnosis by MTB/RIF.